A climate-based analysis of photosynthetically active radiation availability in large-scale greenhouses across China. (15th September 2021) - Wang, Cong; Du, Jiangtao; Liu, Yu; Chow, David
Abstract: Photosynthetically Active Radiation (PAR) is critically required for sustaining plant and vegetable growth. This study investigated PAR availabilities in two typical large-scale greenhouses using an advanced method of climate-based solar modelling in China. Seven Chinese locations in terms of daylight (solar) climate zones and latitudes were studied. The PAR prediction was conducted via RADIANCE (ray-tracing solar and light simulation package). Key findings were: 1) A climate-based analysis was proved as more practical than the methods based on only clear sky and solar geometries. 2) A ray-tracing solar modelling could effectively predict PAR levels at specific positions (e.g. vertical planes), which could benefit the development of vertical farming activities. 3) The PAR availability could receive insignificant impact from roof configuration in these large-scale greenhouses. 4) For the approach of vertical farming, the vertical arrangement of planting system could be significantly affected by greenhouse orientations, while horizontally no such effect can be found. These findings could be developed into design strategies to support greenhouse planning.